Interview with the DG of CIFOR – ICRAF - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2023)
In this interview, Dr Éliane Ubalijoro, CEO of Center for International Forestry Research – World Agroforestry Center (CIFOR – ICRAF), CGIAR's global research and development organizations dealing with forestry and agroforestry shares how CGIAR is deploying innovations to transform food systems in Africa.